STRATEGI PEMBERDAYAAN EKONOMI IBU RUMAH TANGGA MELALUI MENGENAL POTENSI MANGROVE DAN RANCANG INOVASI PRODUK DI DESA KRAMAT - Jevon Ivander Kangsudarmanto; Nadya Josephine Kurniawan; Brandon Devin Purnomo; Mitha Ayu Pratama Handojo (Comm-Edu (Community Education Journal), 2026)
Kramat Village faces a significant decline in the fisheries sector due to the development of the JIIPEindustrial area, which has impacted fishermen's income and compelled housewives to seek alternativesources of livelihood. This community service activity aimed to empower housewives throughtraining on mangrove potential recognition and product innovation design based on local resources.The methods used included pre-test, material presentation, product design practicum sessions,post-test, and appreciation. The activity was attended by 12 target participants at Kramat Village Hall.The material covered identification of safe-to-process mangrove species, processing techniques, andproduct innovation design through group discussions. The training activity demonstrated animprovement in participants’ understanding of mangrove potential, reflected in their increased abilityto identify safe mangrove species and design local resource–based product ideas, as indicated by therise in average scores from 80.8 in the pre-test to 90.8 in the post-test. All participants were able toidentify at least three types of mangroves that can be processed and design innovative product ideas ingroups. This activity serves as the initial step for sustainable entrepreneurship development forhousewives in Kramat Village to improve family welfare independently and competitively through theutilization of local mangrove potential.